The miRNA pathway in neurological and skeletal muscle disease: Implications for pathogenesis and therapy - Sibley, C; Wood, M (2011)
RNA interference (RNAi) represents a powerful post-transcriptional gene silencing network which fine-tunes gene expression in all eukaryotic cells. The endogenous triggers of RNAi, microRNAs (miRNAs), are proposed to regulate expression of up to a third of all protein-coding genes, and have been shown to have critical roles in developmental processes including in the central nervous system and skeletal muscle. Further, many have been reported to display differential expression in various disease states. Here we describe present understanding of the biogenesis and function of miRNAs, review current knowledge of miRNA abnormalities in both human neurological and skeletal muscle disease and discuss their potential as novel disease biomarkers. Finally, we highlight the many ways in which the miRNA pathway may be targeted for therapeutic benefit. © 2011 Springer-Verlag.